Nonlinear Dynamic Behaviors of a Marine Rotor-Bearing System Coupled with Air Bag and Floating-Raft - W. Zhao; M. Li; L. Xiao (Shock and Vibration)
To understand the nonlinear dynamic mechanism of a rotor-bearing system coupled with air bag and floating-raft, the dynamic characteristics of the system are investigated. This work has two key objectives. First, the vibration mechanism of rotor-bearing system coupled with air bag and floating-raft is investigated by developing a numerical model. Then, the nonlinear dynamics of the system and the effect of several parameters are studied, which includes the steady-state response and its spectrum, the orbit and its Poincaré map, the bifurcation diagram, and largest Lyapunov exponent (LLE). The results show that at low speed the dynamic behavior appears in a single periodic motion, and, with the increase of the speed, the motion becomes quasi-periodic and chaotic. These performances indicate that the air bag and floating-raft introduce some dynamic effects of marine rotor-bearing system.